Robert Mearns Yerkes correspondence - Yerkes, Robert Mearns, 1876-1956.
TLS (1945 January 20) from Yerkes to Amram Scheinfeld stating that he is sending Scheinfeld his book, The Dancing Mouse (1907); and carbon copy of a letter (1945 January 24) from Scheinfeld to Yerkes acknowledging receipt of the book and stating that he is sending Yerkes his book, You and Heredity (1939).
Psychologist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Scheinfeld, Amram, -- 1897- -- Correspondence; Psychologists